Environmental Risks in Supply Chain: Recommendations and Directions for Future Research - Arwa, Mukhtar; Awanis, Romli; Abdulgabber, Mansoor Abdullateef; Hael, Al-bashiri (Universiti Malaysia Pahang, 2019)
This paper explores the environmental risks in supply chains and provides recommendations for subsequent studies. Typically, the environmental responsibility is a core part of sustainability which focuses attention directly to protecting and restoring the environment. Furthermore, environmental awareness is essential to design globally distributed supply chain networks. Therefore, the aim of this research is to explore the environmental risks and to identify the available solutions along with a projection of future trends. The basic research steps have been followed to complete this work. The Findings of this research describes the environmental risks that arises during supply chains operations. Furthermore, recommended solutions have been highlighted to address the identified risks. The Blockchain technology is regarded as a suitable solution for the environmental risks issue. The motivation for recommending this technology is its capabilities to contribute effectively towards greening the supply chain operations.